A review of Fiqh Siyasah Tanfidziyyah on the implementation of the mayor regulation on civil servant discipline at the Inspectorate of Bandar Lampung City - Alfina Damar Wulan; Frenki Frenki; Muhammad Jayus (Asy-Syari’ah : Jurnal Hukum Islam, 2026)
This study aimed to analyze the implementation of working hour discipline enforcement for Civil Servant (PNS) based on Article 4 letter (f) of the Mayor of Bandar Lampung Regulation Number 25 of 2021 at the Bandar Lampung City Inspectorate through the perspective of Fiqih Siyasah Tanfidziyyah. The research method used was qualitative field research with a descriptive-analytical approach. Primary data were collected through in-depth interviews with relevant authorities at the Inspectorate, while secondary data were obtained through documentation studies and legal literature. The data analysis technique employed an interactive model comprising data reduction, data display, and conclusion drawing. The results showed that the enforcement of discipline at the Bandar Lampung City Inspectorate ran effectively by utilizing the "Siger" digital attendance application, which minimized data manipulation. The Inspectorate acted as a role model for other agencies with a track record of zero severe violations. The imposition of sanctions prioritized the coaching aspect through tiered reprimands, which is in line with the concept of Ta’zir in Islamic law. From the perspective of Fiqih Siyasah Tanfidziyyah, this policy was a manifestation of the Ulil Amri’s responsibility in realizing public interest (maslahah ‘Ammah) through the principles of trust (amanah), justice, and administrative transparency to improve the quality of public services.